Photoluminescent thermometers based on lanthanide silicates - Mongis, Camille Marie (2020)
The hydrothermal synthesis and structural characterization of lanthanide silicates NaLnSiO4, Ln= Gd3+, Eu3+, Tb3+, Er3+ and Yb3+ are reported. The crystal phase purity of these solid was analysed by powder X-ray diffraction and further characterized by scanning electron microscopy, 29Si MAS NMR, Infra-Red, Raman and photoluminescence spectroscopy. After having determined the best synthesis parameters to obtain the compounds, the suitability of the compounds NaGd1-x-yEuxTbySiO4 and Na[(Gd0.85Yb0.10Er0.05)SiO4 to act as ratiometric photoluminescent thermometers was assessed (Eu3+ and Tb3+ are visible emitters, and Er3+ and Yb3+ infra-red emitters). The Tb3+ to Eu3+ and Yb3+ to Er3+ energy transfers were detected, leading to a temperature dependence of the emission ratio between the Tb3+ 5D4→7F5-0 and Eu3+ 5D0→7F0-4 transitions for NaGd1-x-yEuxTbySiO4 and between Yb3+ 2F5/2→2F7/2 and Er3+ 4I13/2→4I15/2 transitions for Na[(Gd0.85Yb0.10Er0.05)SiO4. This ratio allows the determining the sensitivity of the compounds to act as thermometers. At cryogenic temperatures, the sensitivity obtained depends on the composition parameters x and y for Na[(Gd0.85Yb0.10Er0.05)SiO4. The infrared ratiometric luminescent thermometer NaGd1-x-yErxYbySiO4 presents the best performance in terms of sensitivity